2023
DOI: 10.5194/esurf-11-405-2023
|View full text |Cite
|
Sign up to set email alerts
|

Impacts of human modifications on material transport in deltas

Jayaram Hariharan,
Kyle Wright,
Andrew Moodie
et al.

Abstract: Abstract. As humans continue to inhabit and modify river deltas, the natural processes governing material transport through these landscapes are altered. Two common engineering projects undertaken on deltas are the dredging of channels to enable shipping and the construction of embankments to reduce flooding. While the impact of these topographic modifications has been studied at a local level for specific sites, there is a gap in our generalized understanding of how these landscape modifications impact materi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 89 publications
0
6
0
Order By: Relevance
“…Therefore, it is critical to explore the long-term morphological responses to human intervention in the entire channel network rather than focusing on a single channel reach (Chowdhury et al, 2023;Cox et al, 2021;Wang et al, 2022). The long timescale for recovering the equilibrium (Figures 5 and 7) can lead to significantly cumulative alterations of the water and material supplies to the downstream habitats (Hariharan et al, 2023).…”
Section: Implications For Evolution and Management Of Channel Networkmentioning
confidence: 99%
“…Therefore, it is critical to explore the long-term morphological responses to human intervention in the entire channel network rather than focusing on a single channel reach (Chowdhury et al, 2023;Cox et al, 2021;Wang et al, 2022). The long timescale for recovering the equilibrium (Figures 5 and 7) can lead to significantly cumulative alterations of the water and material supplies to the downstream habitats (Hariharan et al, 2023).…”
Section: Implications For Evolution and Management Of Channel Networkmentioning
confidence: 99%
“…ANUGA was originally developed for coastal applications such as tsunami modeling and has been validated for such applications (Nielsen et al, 2005;Mungkasi and Roberts, 2013). In recent years, ANUGA has been used for delta and coastal river systems along the U.S. Gulf Coast and other similar applications (Tull et al, 2022;Wright et al, 2022a,b;Hariharan et al, 2023). Additional information on this model and its application to the Trinity River can be found in Tull et al (2022).…”
Section: Numerical Model Developmentmentioning
confidence: 99%
“…dorado uses a weighted random walk algorithm adapted from DeltaRCM (Liang et al, 2015a,b) to simulate passive particle transport through model flow fields on a regular grid. It has been used recently in several modeling studies of coastal river and delta systems (Tull et al, 2022;Wright et al, 2022a;Hariharan et al, 2023); more detail on the routing algorithm can be found in the Methods sections of those studies as well as in the software documentation online.…”
Section: Flux and Residence Time Quantification With Doradomentioning
confidence: 99%
“…Coeval delta and crater production was simulated with the pyDeltaRCM numerical model (Moodie et al, 2021), which is a flexible implementation of the widely used DeltaRCM delta model (Liang et al, 2015a). DeltaRCM model design has been robustly validated (Liang et al, 2015a(Liang et al, , 2015b(Liang et al, , 2016 and used to examine delta morphology and evolution under various external forcings and processes (Lauzon & Murray, 2018;Lauzon et al, 2019;Piliouras et al, 2021;Moodie & Passalacqua, 2021;Hariharan et al, 2021Hariharan et al, , 2022Hariharan et al, , 2023. In this article, we do not describe the complete model implementation, and instead provide a high-level overview that highlights model components relevant to our study design and interpretations; a full model description is given in Liang et al (2015a).…”
Section: Delta Modelmentioning
confidence: 99%
“…We ran simulations for 10,000 timesteps, which amounts to 107×10 6 seconds of intermittent bankfull river flow. Parameters and domain scaling were selected based on prior experience with numerical stability in the model, and minimal deviation from a set of parameters commonly used with DeltaRCM (e.g., Liang et al, 2015a;Lauzon & Murray, 2018;Lauzon et al, 2019;Piliouras et al, 2021;Moodie & Passalacqua, 2021;Hariharan et al, 2021Hariharan et al, , 2022Hariharan et al, , 2023. At the end of the simulation, deposits extend 4-5 km into the basin and span 8-10 km perpendicular to the inlet channel (Figure 3e), therefore maintaining an approximately axissymmetric planform over many cycles of channel movement (Parker et al, 1998;Reitz & Jerolmack, 2012;Moodie et al, 2019).…”
Section: Delta Modelmentioning
confidence: 99%